Industrial Revolution Era 4.0: Digital Literacy of Accounting Education Students - Widayati, Ani; Wibawa, Eka Ary; Septiana, Yolandaru; Johari, Razana Juhaida (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
This study aims to find out the different profile of digital literacy skills of four batches of Accounting Education students in the 4th industrial revolution era. As almost all human works will be replaced by robots and only those who have particular skills will be able to survive, it is essential to examine students’ digital literacy skills. A survey employed quantitative approach was conducted with a sample of 175 of four batches Accounting Education students of Universitas Negeri Yogyakarta. The data gathered with questionnaires technique were analysed using descriptive analysis followed with multivariate analysis. The results show that the four batches Accounting Education students have different profile of digital literacy skills in terms of selecting, addressing, and evaluating information. It is suggested for the students to be aware of the changes in digital technology and its contribution to the field of education and consider it as the weapon for them to improve their digital literacy skills.